Analisis Sistem Akuntansi Pemberian Kredit Gadai dalam Mencegah terjadinya Kredit Macet terhadap UMKM pada PT. Pegadaian (Persero) Unit Pelayanan Syariah Cikijing - Rahmat Yuliansyah (Jurnal Manajemen, 2018)
This study aims to find out the accounting system and procedure of providing mortgage loans for Micro Small Medium Enterprises (MSMEs) and to know how to prevent the occurrence of bad loans at PT. Pegadaian (Persero) Cikijing Sharia Service Unit. This research uses descriptive research type, using qualitative research method. The data used in this research are primary data and secondary data. With data collection techniques through field studies (field research) is done by way of documentation and interviews with the Head of Branch Office PT. Pegadaian (Persero) Cikijing Sharia Service Unit. The data obtained through documentation and interviews first processed using software application program that is Microsoft Office then presented in the form of description and data table. The results showed that the accounting system and procedure of receiving mortgage loans for MSMEs or Ar-rum in PT. Pegadaian (Persero) Cikijing Sharia Service Unit has been run well. Starting from the application stage by the prospective customer, the completeness check phase of the requirements, the stage of assessment, approval or termination stage, and the contract stage and fund disbursement. To prevent the occurrence of bad credit using 4C analysis method Character (character), Capacity (capability), Capital (capital), and Collateral (guarantee). Efforts and management of non-performing loans are conducted by way of Somasi, insurance claims against problem loans, withdrawal of guarantee goods and the execution of collateral goods.